Pretty boys are poisonous : poems - Fox, Megan, 1986- (Gallery Books, an imprint of Simon & Schuster, Inc., 2023)
"Megan Fox showcases her wicked humor throughout a heartbreaking and dark collection of poetry. Over the course of more than seventy poems Fox chronicles all the ways in which we fit ourselves into the shape of the ones we love, even if it means losing ourselves in the process."--Amazon.